2015
DOI: 10.1377/hlthaff.2015.1281
|View full text |Cite
|
Sign up to set email alerts
|

Direct Primary Care: Concierge Care For The Masses

Abstract: Direct care: Doug Nunamaker, a physician with Atlas Medical, a direct primary care practice in Wichita, Kansas, discusses weight management, body mass index, and health issues with a patient, Jeanette Reeder. Atlas charges a monthly membership fee and does not bill insurers for the care it provides. Each physician in the practice sees about 500 patients-far fewer than most traditional practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…18,19 At the same time, more physicians, particularly those providing primary care, are considering or have moved into concierge practice in response to treatment time constraints and work effort-compensation concerns. 20,21 In light of structural changes in the physician labor market, we report on a national survey of practicing physicians that assessed their perceptions of pay fairness. Specifically, we hypothesized that physicians who think their compensation is fair will be more satisfied at work, be less inclined to leave their medical practice, and report having better overall health.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 At the same time, more physicians, particularly those providing primary care, are considering or have moved into concierge practice in response to treatment time constraints and work effort-compensation concerns. 20,21 In light of structural changes in the physician labor market, we report on a national survey of practicing physicians that assessed their perceptions of pay fairness. Specifically, we hypothesized that physicians who think their compensation is fair will be more satisfied at work, be less inclined to leave their medical practice, and report having better overall health.…”
Section: Introductionmentioning
confidence: 99%
“…Although GPs do not fulfill a formal compulsory gatekeeper function in Germany, their availability and accessibility play a crucial role in a populations’ access to health care [6, 37]. Hence, it can be assumed that an unbalanced distribution of GPs could translate into health inequities [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, membership fees affect accessibility as a barrier to those unable or unwilling to make monthly payments for primary care. Many physicians who practice in DPC models have argued that it is incorrect to assume that the remaining eligible population is systematically less vulnerable both physically and financially 5,[15][16][17][18] ; however, the assertion that DPC patients are representative of the socioeconomic and health status of a given community has not been demonstrated. For example, Alexander and col- …”
Section: Structurementioning
confidence: 99%
“…3,5 By one count, there are currently at least 723 DPC practice locations in 48 states. 6 A survey conducted by the American Academy of Family Practice found that 2% of respondents reported practicing in a DPC model, with another 7% considering a move to DPC in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation